The Effect of Transformational Leadership, Physical Work Environment Internal, on Employee Job Satisfaction Mediated by Work Life Balance at PT. XYZ - Silaban, Herlina Yolanda; Setyaningrum, Retno Purwani (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
Employee job satisfaction is one of the important things for a company; therefore, the company will always try to increase employee satisfaction. This study was conducted to determine the level of satisfaction at PT. XYZ by looking at the relationship between transformational leadership, internal physical work environment, and work-life balance on employee job satisfaction at PT. XYZ. The purpose of this study was to analyze the effect of Transformational Leadership, Internal Physical Work Environment, on Employee Job Satisfaction with Work Life Balance as a mediating variable at PT. XYZ. This study uses a quantitative method. There are 135 employees at XYZ company; however, 60 respondents have correctly filled out the questionnaire distributed, so these 60 respondents are the sample. The data was collected using Google Forms. Data management is carried out using Partial Least Square (PLS) through the Structural Equation Model (SEM) technique with the help of the SmartPLS version 4.1.1 program. The results of the analysis obtained are that transformational leadership has been proven to affect employee job satisfaction, internal physical work environment has been proven to affect employee job satisfaction, transformational leadership has not been proven to affect work life balance, internal physical work environment has been proven to affect work life balance, work life balance has not been proven to affect employee job satisfaction, transformational leadership has not been proven to affect employee job satisfaction mediated by work life balance, internal physical work environment has not been proven to affect employee job satisfaction mediated by work life balance at PT. XYZ.